Effect of Irregular Treatment on Severity of Osteoporosis in Rheumatoid Arthritis Patients - Abdulkareem Raoof Al-Shaibani , Saif (Diyala Journal of Medicine, 2021)
Background:Rheumatoid arthritis is a chronic systemic inflammatory disorder that is associated with progressive disability and systemic complications. One of these complications is osteoporosis. Patients with severe osteoporosis have one or more fragility fractures in addition to T-score -2.5 or lower. Osteoporosis is more prevalent in rheumatoid arthritis patients who have higher disease activity. Objective: To show the effect of irregular treatment in patients with rheumatoid arthritis on the severity of osteoporosis. Patients and Methods: A cross-sectional study enrolled a total of 40 female patients who had rheumatoid arthritis. The data collected from patients include disease duration, disease activity and patients’ compliance to their drugs. They were sent to dual-energy x- ray absorptiometry scan and results were recorded. Results: The mean age was 45.95 ± 10.0 years; 45% of them had rheumatoid arthritis for less than five years; 55% had a low level of disease activity; and 65% of them had received treatment irregularly. Osteoporosis was diagnosed in 60% of them and 41.7% of them had severe osteoporosis. The highest prevalence of osteoporosis among patients with rheumatoid arthritis was seen significantly among older patients, patients with longer duration of rheumatoid arthritis, those with higher activity of rheumatoid arthritis, and those with irregular treatment. More than half of those who received treatment irregularly had severe osteoporosis with a significant association between treatment regularity of rheumatoid arthritis and severity of osteoporosis. Conclusion: Severe osteoporosis occurs in rheumatoid arthritis patients with a history of irregular treatment which occurs either due to patient incompliance or delay in diagnosis. Osteoporosis is more prevalent in rheumatoid arthritis patients with longer disease duration, older age, higher disease activity and those who received treatment irregularly.